Effects of vertical wind shear on intensities of mesoscale convective systems over West and Central Africa. (24th April 2022) - Baidu, Michael; Schwendike, Juliane; Marsham, John H.; Bain, Caroline
Abstract: Vertical wind shear is known to play a key role in the organization and intensity of mesoscale convective systems (MCSs) in West and Central Africa. A decadal increase in vertical wind shear has recently been linked to a decadal increase in intense MCSs over the Sahel. Here, the effects of vertical wind shear on MCSs over West and Central Africa have been investigated using a 10‐year (1998–2007) MCS dataset. Strong vertical shear is associated with long‐lived, moderate speed, moderate size and cold (deep) storms with high rain rates. The observed cloud top heights of storms over the oceans are closer to their level of neutral buoyancies (LNBs) compared to their land counterparts on the same latitudes. We hypothesize that this is due to greater entrainment dilution over land compared to storms over the ocean. Vertical shear allows storm anvils to reach higher altitudes relative to their LNB, this is consistent with the colder top storms over the Sahel (a region with a high vertical shear) compared to the Congo, despite a higher LNB in the Congo. It is not possible to diagnose the exact mechanisms for this impact of vertical shear from the data, but it is consistent with recent work showing that shear reduces entrainment dilution of squall‐line updrafts. We conclude that modelling impacts of vertical shear, which are normally missed in convection parameterizations, are not only important for predictions of high impact weather, but also for modelling the mean distribution of storm heights across Africa. Abstract : (a) Brightness temperature difference (BTavg – temperature at the level of neutral buoyancy (LNB), oC) and (b) vertical wind shear associated with MCSs (1998–2007;ms −1 ). The associated 925‐hPa winds (arrows, ms −1 ) and the wind shear of 8ms −1 (burgundy contours) are overlaid.